Status Kesuburan Tanah Pada Lahan Pokem (Setaria italic L., Beauv) di Kampung Bawei Distrik Numfor Timur - Nollince Novita Merani; Kati Syamsudin Kadang Tola; Siti Hadjar Kubangun (Agrotek, 2015)
Pokem (Papuas’s wheat) is an endemic plant origin from Numfor island. Cultivation of pokem is traditionaly, small scale, and without the addition of fertilizer. This study aims to determine the status of soil fertility in the land of pokem in Bawey village at district of Eastern Numfor. Results from this study are expected to be the initial information for improving and developing crop production of pokem and other agricultural crops. The method used in this research is descriptive method, with the technique of field observation and laboratory analysis. The analysis showed that, the soil physical in location research dominated by sandy clay loam texture with subangular blocky structure. The chemical soil are neutral of pH, CEC and K classified as very low, N-total low to moderate, Ca ranged from low to very low, low Mg, Na very low to high and very high of KB. Based on the results of the analysis of soil properties and criteria for assessment of the Soil Research Center (1983) the status of soil fertility at study sites classified as very low.